Efek Ekstrak Biji Alpukat (Persea americana Mill) sebagai Antihiperkolesterol Darah Mencit (Mus musculus) - Jannah, Wardatul; Rahman, Nurdin; Ratman, Ratman (Jurnal Akademika Kimia, 2017)
Cholesterol is an important element in the body needed to regulate chemical processes in the body, but high amounts of cholesterol can lead to atherosclerosis which ultimately will have an impact on coronary heart disease. This study aims to know phytochemicals contained in an avocado (persea americana mill) seeds’ extract and determines the concentration of the avocado (persea americana mill) seeds’ extract can lower mice’s blood (mus musculus) hyper cholesterol levels in optimum. The animals tested were male mice which totaled 15 mice induced by propylthiouracil and high-fat feed. The mice were divided into 5 groups with different treatment. The treatment I, II, and III were given avocado seeds’ extract with a concentration of 10%, 20% and 40% respectively, treatment IV was given simvastatin as a positive control (+), and treatment V was given standard food and aquades as negative control (-). The data gained was analyzed through analysis of variance (ANOVA) statistical test which was followed by Duncan’ stest. The research findings show that avocado seeds’ extract is considered as positive to contain flavonoids, saponins, and tannins. The concentration of the avocado seeds’ extract which lowers blood hypercholesterol levels in an optimum way is 10% (b/v).